2009
DOI: 10.1007/s10295-009-0673-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of gibberellin A4 (GA4) by a mutant of Gibberella fujikuroi in wheat gluten medium

Abstract: Mutants of Gibberella fujikuroi with different colony characteristics, morphology and pigmentation were generated by exposure to UV radiation. A mutant, Mor-189, was selected based on its short filament length, relatively high gibberellin A(4) (GA(4)) and gibberellin A(3) (GA(3)) production, as well as its lack of pigmentation. Production of GA(4) by Mor-189 was studied using different inorganic and organic nitrogen sources, carbon sources and by maintaining the pH of the fermentation medium using calcium carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
(40 reference statements)
0
11
1
1
Order By: Relevance
“…It was observed that GA production initiated on the first day of fermentation, which is contrary to reports that GA commences about 46 h after the initiation of fermentation following nitrogen depletion in the medium (Escamilla et al, 2000;Rodrigues et al, 2009;Rios-Iribe et al, 2011). However, Lale and Gadre (2010) also reported GA production at 20 h by a mutant of G. fujikuroi. Maximum GA yields are reported to be between days 4 and 8 of fermentation for F. moniliforme (Kumar and Lonsane, 1990;Meleigy and Khalaf, 2009;Rangaswamy, 2012;Omojasola and Benu, 2016) and day 6 and 12 for A. niger (Bilkay et al, 2010).…”
Section: Resultscontrasting
confidence: 74%
“…It was observed that GA production initiated on the first day of fermentation, which is contrary to reports that GA commences about 46 h after the initiation of fermentation following nitrogen depletion in the medium (Escamilla et al, 2000;Rodrigues et al, 2009;Rios-Iribe et al, 2011). However, Lale and Gadre (2010) also reported GA production at 20 h by a mutant of G. fujikuroi. Maximum GA yields are reported to be between days 4 and 8 of fermentation for F. moniliforme (Kumar and Lonsane, 1990;Meleigy and Khalaf, 2009;Rangaswamy, 2012;Omojasola and Benu, 2016) and day 6 and 12 for A. niger (Bilkay et al, 2010).…”
Section: Resultscontrasting
confidence: 74%
“…The GA4 peak is below the limit of quantification of the calibration curve; therefore, it could not be determined, may be due to the low concentration of gibberellin A4 and the interfering substances present in the fresh tissue [1] [2] [9]. In order to achieve the concentration of gibberellin and a good peak separation, the sample was subjected to drying in oven.…”
Section: Fresh Samples Of Dasylirion Cedrosanummentioning
confidence: 99%
“…The mixture GA4+GA7 has shown good results [1] [11]- [13]. However, in the last few years there has been increased commercial interest in the production and separation of GA4 and GA7 due to their horticultural uses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations